Analysis of Digital Divide in Mastery of ICT in Palangka Raya City - Purmasari Purmasari Purmasari; Djoko Budiyanto Setyohadi; Albertus Joko Santoso (Aceh International Journal of Science and Technology, 2018)
This study aims to measure the digital divide by analyzing the influencing factors of the divide (gap) and the effectiveness of ICT public services in Palangka Raya City. The method used for measuring the digital divide in this study was the SIBIS method, the result of the activities of the European Commission which is used for analyzing and comparing different indicators and adapted to environmental conditions. The SIBIS GPS (General Population Survey) indicator was used in this study included the availability of ICT access, ICT utilization, and levels of ICT and e-government capability. The population in this study was the people of Palangka Raya City with a sample of 399 respondents. The results of digital divide measurement in this study showed that the level of digital divide as seen from the aspects of access availability, utilization and level of ICT capability was at medium category, the level of digital divide as seen from the aspect of e-government was in low category, and the level of digital divide as seen from the aspect of demography showed a clear distinction to the digital divide in Palangka Raya City